2021
DOI: 10.3390/ijerph18105448
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Psychophysiological Stress and Socio-Emotional Competencies on the Clinical Performance of Nursing Students during a Simulation Practice

Abstract: Psychophysiological stress can affect the cognitive response and effective learning of students during medical simulation practices. This study aimed to explore the effect of psychophysiological stress and socio-emotional competencies on clinical performance during a simulation experience. A pre-test/post-test design was used to assess physiological (blood pressure, heart rate and blood oxygen saturation) and psychological parameters (stress and anxiety) as well as socio-emotional skills (cognitive load, self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 50 publications
4
12
0
6
Order By: Relevance
“…The sympathetic response of the autonomous system leads to an increase in BP and HR. In some research, these physiological markers had negative relationships with blood oxygen saturation [ 32 ]. Some previous studies have reported that smelling or massaging essential oils such as ylang-ylang, bitter orange, and lavender could reduce HR [ 33 ], and a pleasant smell could bring a decrease in HR [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sympathetic response of the autonomous system leads to an increase in BP and HR. In some research, these physiological markers had negative relationships with blood oxygen saturation [ 32 ]. Some previous studies have reported that smelling or massaging essential oils such as ylang-ylang, bitter orange, and lavender could reduce HR [ 33 ], and a pleasant smell could bring a decrease in HR [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Investigating the potential in uence of perceived stress on estimated learning success among AP, we were able to demonstrate that the factor "sense of control" revealed a typical inverse U-shaped correlation to both subtypes of "estimated learning success", resembling the relationship that Yerkes and Dodson described for arousal and performance in challenging tasks (Yerkes and Dodson, 1908). According to one study we found in the literature, stress responsiveness was a predictor of good performance (Keitel et al, 2011), while most work highlights the impairment of cognitive skills under excessive stress in high-delity surgical or medical emergency simulations (Mauriz et al, 2021;McGraw et al, 2013;Wetzel et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Tutees recognized simulation as a stressful task, but as tutors supported them not only with knowledge and nursing skills but emotionally, their pressure was relieved, and they became confident through the positive reinforcement from tutors during the process. Despite the positive learning effect of simulations, students experience high levels of stress and anxiety during simulations, negatively affecting their self-efficacy and learning results [ 24 ]. Using peer tutoring during simulations is effective in increasing learning efficacy by reducing tutees' anxiety [ 25 ].…”
Section: Discussionmentioning
confidence: 99%